Cytologic categorization of pancreatic neoplastic mucinous cysts with an assessment of the risk of malignancy: A retrospective study based on the Papanicolaou Society of Cytopathology guidelines. Issue 4 (30th November 2015) - Smith, Amber L.; Abdul‐Karim, Fadi W.; Goyal, Abha
Abstract : BACKGROUND: Cytology plays a pivotal role in the preoperative diagnosis of pancreatic cysts. Here the Papanicolaou Society of Cytopathology (Pap Society) guidelines were used to reclassify and assess the malignancy risk of cytology diagnoses of histologically proven pancreatic neoplastic mucinous cysts. METHODS: A database search (January 2000 to June 2014) was performed for pancreatic neoplastic mucinous cyst resections with endoscopic ultrasound–guided fine‐needle aspiration within the preceding year. Histologic diagnoses were reclassified according to the 2010 Word Health Organization criteria. For atypical/suspicious/positive cytology diagnoses, the cytology slides were reviewed, blinded to the histologic diagnoses. The cysts were reclassified according to the Pap Society guidelines, and the findings were correlated with the histology. RESULTS: One hundred thirty‐eight cases of pancreatic neoplastic mucinous cysts were retrieved. Eleven cases with atypical/suspicious cytology diagnoses with unavailable slides were excluded. The remaining 127 cases included 81 intraductal papillary mucinous neoplasms and 46 mucinous cystic neoplasms. The sensitivity of cytology for the diagnosis of neoplastic mucinous cysts was 76.4%. The sensitivity, specificity, and accuracy of cytology for the diagnosis of malignancy (high‐grade dysplasia or worse) were 48.3%, 94.9%, and 84.3%, respectively. The risk of malignancy was 17.4% for the nondiagnostic category, 0% for the negative category, 13% for the neoplastic category, 63.6% for the atypical category, 80% for the suspicious category, and 100% for a positive diagnosis. CONCLUSIONS: This study reveals that the Pap Society guidelines allow the accurate categorization of pancreatic neoplastic mucinous cysts with cytology. The diagnostic categories (from negative to positive) are associated with an increasing risk of malignancy, and this can further aid in patient management and risk stratification. Cancer Cytopathol 2016;124:285–93 . © 2015 American Cancer Society . Abstract : This study retrospectively categorizes pancreatic neoplastic mucinous cysts according to the Papanicolaou Society of Cytopathology guidelines for reporting pancreaticobiliary cytology. The findings reveal that this categorization is accurate and is associated with an increasing risk of malignancy, and this can further aid in patient management and risk stratification.